Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the given system of linear equations:
[tex]\[ \begin{array}{l} 5x + 2y = 22 \\ -2x + 6y = 3 \end{array} \][/tex]
we can use the substitution or elimination method. Here, the elimination method can be particularly effective. Follow these steps to find the solution:
1. First equation:
[tex]\[ 5x + 2y = 22 \][/tex]
2. Second equation:
[tex]\[ -2x + 6y = 3 \][/tex]
For elimination, align the equations to eliminate one of the variables.
3. Multiply the first equation by 3 to align the coefficients of [tex]\( y \)[/tex] in both equations:
[tex]\[ 3(5x + 2y) = 3(22) \][/tex]
This simplifies to:
[tex]\[ 15x + 6y = 66 \][/tex]
4. Now, we have:
[tex]\[ \begin{array}{l} 15x + 6y = 66 \\ -2x + 6y = 3 \end{array} \][/tex]
5. Eliminate [tex]\( y \)[/tex] by subtracting the second equation from the first:
[tex]\[ (15x + 6y) - (-2x + 6y) = 66 - 3 \][/tex]
Simplifying this, we get:
[tex]\[ 15x + 6y + 2x - 6y = 63 \][/tex]
[tex]\[ 17x = 63 \][/tex]
6. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{63}{17} \][/tex]
7. Convert this to a decimal and round to the nearest tenth:
[tex]\[ x \approx 3.7 \][/tex]
So, the [tex]\( x \)[/tex]-coordinate of the solution is:
[tex]\[ \boxed{3.7} \][/tex]
[tex]\[ \begin{array}{l} 5x + 2y = 22 \\ -2x + 6y = 3 \end{array} \][/tex]
we can use the substitution or elimination method. Here, the elimination method can be particularly effective. Follow these steps to find the solution:
1. First equation:
[tex]\[ 5x + 2y = 22 \][/tex]
2. Second equation:
[tex]\[ -2x + 6y = 3 \][/tex]
For elimination, align the equations to eliminate one of the variables.
3. Multiply the first equation by 3 to align the coefficients of [tex]\( y \)[/tex] in both equations:
[tex]\[ 3(5x + 2y) = 3(22) \][/tex]
This simplifies to:
[tex]\[ 15x + 6y = 66 \][/tex]
4. Now, we have:
[tex]\[ \begin{array}{l} 15x + 6y = 66 \\ -2x + 6y = 3 \end{array} \][/tex]
5. Eliminate [tex]\( y \)[/tex] by subtracting the second equation from the first:
[tex]\[ (15x + 6y) - (-2x + 6y) = 66 - 3 \][/tex]
Simplifying this, we get:
[tex]\[ 15x + 6y + 2x - 6y = 63 \][/tex]
[tex]\[ 17x = 63 \][/tex]
6. Solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{63}{17} \][/tex]
7. Convert this to a decimal and round to the nearest tenth:
[tex]\[ x \approx 3.7 \][/tex]
So, the [tex]\( x \)[/tex]-coordinate of the solution is:
[tex]\[ \boxed{3.7} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.